Best Practice in Distance Learning with Experimental Demonstration on the Concept of the Automotive Brake Pad Fabrication from Domestic Waste to Vocational Students for Supporting Education for Sustainable Development - Ragadhita, Risti; Nandiyanto, Asep Bayu Dani; Maryanti, Rina; Al Husaeni, Dwi Fitria; Al Husaeni, Dwi Novia; Fiandini, Meli; Mudzakir, Ahmad; Hufad, Achmad; Masek, Alias (Journal of Technical Education and Training, 2023)
The aim of this study was to determine the best practice of using distance learning with conventional teaching methods and experimental demonstration methods to teach vocational students about the concept of fabricating automotive brake pad systems from domestic waste. This study employs an experimental design with pre- and post-test control groups to class-XI vocational students. We taught vocational students about brake pad fabrication and its industrial applications. Conventional methods of instruction were used in the control class, while the experimental demonstration method with learning videos was used in the experimental class. The learning videos used in the experimental class during the learning process contain basic theory and experiments on related materials. The results of the pre-test and post-test scores were analysed and measured to determine student learning outcomes. The findings revealed differences in learning outcomes between the control and experimental groups. Students in the experimental group comprehended the concept of fabricating brake pads more thoroughly than students in the control group. Students can get concrete examples from the teacher or instruction through experimental demonstration. Practical experience can help to form strong memories and skills. This success can be attributed to the availability of learning videos that students can watch repeatedly. Students are also more enthusiastic about learning videos because we teach something that can be applied in the industry. The addition of experimental demonstrations using commercially available materials increases student interest by increasing students' ability to experiment on their own. In addition, we also explain the concept of recycle and reuse agricultural waste for fabricating brakepad that can support current sustainable development goals (SDGs). Further learning applications using experimental demonstration methods are expected to be carried out because this method is proven to be effective for student learning.